Effects of Combretum micranthum, Xienmia americana and Aloysia citrodora Leaf Extracts against Oviposition and Egg Viability of Anopheles gambiae S.L. (Diptera: Culicidae) (Sahel Journal of Life Sciences FUDMA, 2024)
The study investigated the oviposition and egg viability effects of leaf extracts from Combretum micranthum, Xienmia americana, and Aloysia citrodora on female Anopheles gambiae mosquitoes. Leaves were sourced from Goron-maje Town, Dambatta LGA, Kano State, and extracts were prepared using ethanol, methanol, and ethyl-acetate. Bioassays were conducted at ambient temperature and relative humidity, testing oviposition activity and egg viability. Ethyl-acetate extracts, particularly from A. citrodora, significantly reduced oviposition compared to controls, with a 42.85% decrease. Ethanol extract of C. micranthum also showed reduced oviposition (8.84%). Significant differences were observed in the effects of different concentrations (ppm/mL) of plant extracts compared to controls. X. americana ethanol leaf extract at 20.0 ml concentration showed a 10% decrease in egg viability, while Combretum micranthum extracts at 20.0 ml and 30.0 ml concentrations showed 40.0% and 26.0% reductions in viability respectively. Aloysia citrodora methanol extracts exhibited a lower effect (48.0%) on viability compared to controls. X. americana ethanol leaf extract at 10% concentration significantly reduced hatching ability (26Â±06.21). Similarly, ethanol and ethyl-acetate extracts of C. micranthum and A. citrodora at 20.0 ml and 30.0 ml concentrations showed decreased hatching abilities compared to controls. The study suggests that ethanol and ethyl-acetate extracts of X. americana, C. micranthum, and A. citrodora could be effective and safer methods for mosquito control.